Proceedings of the 6th annual SEAAIR conference : transforming higher education for the knowledge society, 5-7 September, 2006, Awana Porto Malai Resort, Langkawi, Malaysia - SEAAIR Annual Conference (6th : 2006 : Langkawi, Malaysia); South East Asian Association for Institutional Research (Kuala Lumpur : SEAAIR (South East Asian Association for Institutional Research), 2006)
Includes references.